NITRATO ADDUCTS AND DERIVATIVES: SYNTHESIS AND INFRARED STUDY - MOUHAMADOU BIRAME DIOP; LIBASSE DIOP (Journal of Engineering Studies and Research)
Five new nitrato adducts and derivatives have been synthesized and studied by infrared spectroscopy. The suggested structures are discrete or of infinite chain type, the nitrate behaving as a bidentate or a monodentate ligand, the environment around the tin (IV) centres being octahedral or trigonal bipyramidal. When extra hydrogen bonds are considered supramolecular architectures may be obtained.